PERAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DAN BUDAYA SEKOLAH DALAM MEMODERASI PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU SMK SWASTA KELOMPOK TEKNOLOGI DI KECAMATAN PATI KOTA (Students' Journal of Economic and Management, 2013)
The purpose of this study to determine the effect of  work motivation and competency on teacher’s performance moderated by the transformational leadership and school culture. This research was conducted with random sampling method. Population and quantity of this research is 109 teacher. The object of this research is Vocational High School technology group in Pati. The equipment which is used in this research is computer software program SPSS ver. 16 and that used regression analysis approach. From the analysis and discussion show that a significant positive influence motivation on performance, significantly positive effect of competency on performance. transformational leadership has not moderating the influence of motivation on the performance of teachers. transformational leadership  has  moderating the influence of competency on the performance of teachers. School culture has not moderating the influence of motivation on the performance of teachers, school culture has not moderating the influence of competency on the performance of teachers   Keywords: Motivation, Competency, Transformational Leadership, School Culture  and Performance.